A coupled effect of nuclear and electronic energy loss on ion irradiation damage in lithium niobate. (15th February 2016) - Liu, P.; Zhang, Y.; Xue, H.; Jin, K.; Crespillo, M.L.; Wang, X.; Weber, W.J.
Abstract: Understanding irradiation effects induced by elastic energy loss to atomic nuclei and inelastic energy loss to electrons in a crystal, as well as the coupled effect between them, is a scientific challenge. Damage evolution in LiNbO3 irradiated by 0.9 and 21 MeV Si ions at 300 K has been studied utilizing Rutherford backscattering spectrometry in channeling mode. During the low-energy ion irradiation process, damage accumulation produced due to elastic collisions is described utilizing a disorder accumulation model. Moreover, low electronic energy loss is shown to induce observable damage that increases with ion fluence. For the same electronic energy loss, the velocity of the incident ion could affect the energy and spatial distribution of excited electrons, and therefore effectively modify the diameter of the ion track. Furthermore, nonlinear additive phenomenon of irradiation damage induced by high electronic energy loss in pre-damaged LiNbO3 has been observed. The result indicates that pre-existing damage induced from nuclear energy loss interacts synergistically with inelastic electronic energy loss to promote the formation of amorphous tracks and lead to rapid phase transformation, much more efficient than what is observed in pristine crystal solely induced by electronic energy loss. This synergistic effect is attributed to the fundamental mechanism that the defects produced by the elastic collisions result in a decrease in thermal conductivity, increase in the electron-phonon coupling, and further lead to higher intensity in thermal spike from intense electronic energy deposition along high-energy ion trajectory. Graphical abstract: The ( f d, n & f d, e ) represents the Nb-disorder at LiNbO3 surface induced by the sequential low energy Si + and high energy Si 7+ irradiations. The ( f d, n + f d, e ) means the sum of the Nb-disorders induced by the low energy Si + and high energy Si 7+ irradiations, respectively. The difference of the Nb-disorder between ( f d, n & f d, e ) and ( f d, n + f d, e ) clearly shows the damage increase during the sequential low energy Si + and high energy Si 7+ irradiations and demonstrates the coupled effect between the nuclear energy loss during the low energy ion irradiation and the electronic energy loss during the high energy ion irradiation.